Pengelolaan Pembelajaran Blended Learning Masa Covid 19 - Naharani, Ita; Saefudin, Saefudin (Universitas Islam Negeri Walisongo, 2024)
The purpose of this study is to find out the management of blended learning at SD Supriyadi Semarang which is focused on 3 parts, namely material management, process, and results. This research approach uses qualitative descriptive research. This research was carried out at SD Supriyadi Semarang. The subjects of this study are teachers and students at SD Supriyadi Semarang. The data collection technique uses observation, interview and documentation techniques. The data validity technique uses source triangulation. The data analysis technique uses data reduction methods, data presentation and conclusion drawn. The results of the study show that the management of blended learning has not been carried out well. This study found that (1) The management of blended learning materials has not been carried out well, teachers do not try to distinguish the materials used in blended learning. (2) The management of the blended learning process has not been maximized. Teachers do not understand classroom management. (3) The management of blended learning outcomes has not been maximized, there is a tendency for teachers to emphasize learning outcomes more on cognitive aspects and less touching on affective aspects. Therefore, teachers at SD Supriyadi Semarang need to conduct a review so that the material presented is in accordance with the provisions. Teachers as educators must understand classroom management in blended learning. In the management of learning outcomes, teachers should apply three-aspect assessment and not lean towards only one aspect. In addition, the school should hold a dilkat for teachers so that teachers can do this blended learning well. This research recommends increasing teacher competency in blended learning management to support more effective and comprehensive learning. For future research, it is expected to expand the variables and research objects and is expected to use more research literature